Analisis Penerapan Etika Kerja dalam Lingkungan Kantor pada Pegawai Pemeritah Desa: Studi pada Desa Ciwaruga, Kab. Bandung Barat, Indonesia - Wini Nuraeni; Nisa Sahara (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
Work ethics play a crucial role in shaping the quality, accountability, and professionalism of public services, particularly at the village government level where direct interaction with the community is intensive. This study aims to analyze the implementation of work ethics among employees of the Ciwaruga Village Office, West Bandung Regency, and to identify the supporting and inhibiting factors that affect its application in public service delivery. This research employs a qualitative descriptive approach using in-depth interviews, observation, and documentation. The informants consist of six village employees and three residents as service recipients. The findings indicate that work ethics have been applied relatively well, as reflected in employees’ discipline, responsibility, ethical communication, and professional appearance. Digital attendance systems, exemplary leadership, and the availability of standard operating procedures support the formation of a positive work culture. However, emotional instability, overly informal work culture, and employees’ health conditions were identified as challenges that affect ethical consistency. Overall, the implementation of work ethics positively contributes to service quality, public trust, and the institutional image of village governance. This study recommends strengthening ethical training and optimizing digital service systems to enhance the professionalism of village apparatus.